Extracellular matrix alterations in late-onset Fuchs' corneal dystrophy - Weller, Julia M.; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Bachmann, Björn; Tourtas, Theofilos; Kruse, Friedrich (Investigative Ophthalmology & Visual Science, 2014)
To characterize the alterations of extracellular matrix proteins in Descemet's membranes (DM) of patients with late-onset Fuchs' corneal dystrophy (FCD) and to differentiate them from nonspecific alterations in pseudophakic bullous keratopathy (PBK).Human DM-endothelial cell complexes were obtained from patients with late-onset FCD (n = 40), PBK (n = 6), and control eyes (n = 5). Gene expression profiles of endothelial cells were compared using a commercial real-time PCR array and quantitative real-time PCR assays for confirmation of differentially expressed genes. A total of 24 extracellular matrix proteins were also localized in cryosections of corneal specimens from FCD (n = 10), PBK (n = 4), and control eyes (n = 5) by immunohistochemistry.Polymerase chain reaction array analysis revealed a significant upregulation of 27 out of 84 extracellular matrix-related genes including collagens, proteoglycans, glycoproteins, cell adhesion molecules, and matrix metalloproteinases in FCD specimens as compared to normal controls, which could be partly confirmed and quantified by real-time PCR. Comparative analysis of FCD and PBK specimens showed a significant and consistent FCD-specific upregulation of collagen types I, III, and XVI; fibronectin; agrin; clusterin; transforming growth factor beta-induced (TGFBI); and integrin ?4 (3- to 18-fold, P < 0.05). Immunohistochemistry revealed an increased labeling of collagen (types III, VII, XV, XVI), agrin, fibulin-2, TGFBI, versican, and clusterin in the DM of FCD specimens compared to PBK specimens.The findings provide evidence for a specific upregulation, production, and deposition of collagen types III and XVI, agrin, TGFBI, and clusterin in late-onset FCD and thus point to the importance of matrix alterations in the pathophysiology of FCD.
EVALuna2:21180